2001
DOI: 10.1038/sj.mp.4000808
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the NMDAR2B (GRIN2B) gene in schizophrenia

Abstract: NMDA receptor dysfunction may be involved in the pathophysiology of schizophrenia. Based on this hypothesis, we screened 48 Japanese patients with schizophrenia for mutations in the coding region of the NMDAR2B subunit gene (GRIN2B). An association study between the identified DNA sequence variants and schizophrenia was performed in 268 Japanese patients with schizophrenia and 337 Japanese control subjects. Eight single nucleotide polymorphisms were detected, all of which were synonymous. The association sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
3
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 30 publications
6
71
3
5
Order By: Relevance
“…3, available online only), we did not find any strong haplotype structure for SNPs 2664C/T, 4197T/C, and 5988T/C, although they were previously reported to be in almost complete LD with SNPs 1665C/T and 5806A/C. 21 None of the three individual markers (366C/G, 2664C/T, and 5988T/C) provided significant evidence. Both allele and haplotype frequencies may vary around the world, and the markers could be in LD with different haplotypes in different populations.…”
Section: Discussionmentioning
confidence: 62%
“…3, available online only), we did not find any strong haplotype structure for SNPs 2664C/T, 4197T/C, and 5988T/C, although they were previously reported to be in almost complete LD with SNPs 1665C/T and 5806A/C. 21 None of the three individual markers (366C/G, 2664C/T, and 5988T/C) provided significant evidence. Both allele and haplotype frequencies may vary around the world, and the markers could be in LD with different haplotypes in different populations.…”
Section: Discussionmentioning
confidence: 62%
“…44 An overlap in genetic susceptibility for schizophrenia and BPI has been argued by many investigators and was recently reviewed by Craddock et al 45 We agree that there is strong evidence for an overlap of genetic factors contributing to these two phenotypes, and we recently published a candidate gene association study 17 that investigated 440 SNPs in 64 functional and positional candidates for both disorders, genotyped in two sets of triads of AJ descent ascertained for either BPI or schizophrenia. Although at that time studies had suggested GRIN2B only as a candidate for schizophrenia, 40,41 in our study, it was among the best findings for BPI. More recently, a study by Martucci et al 23 also detected an association between GRIN2B DNA variants and both BP and schizophrenia, and a metaanalysis supported the association with schizophrenia.…”
Section: Discussionmentioning
confidence: 66%
“…A positive association between schizophrenia and variants in coding exons and variants in the 3′-untranslated region of the NR2B gene suggests that the NR2B gene locus, when in linkage disequilibrium with these regions, confers susceptibility to schizophrenia. 18 Whether these variants and the T-200G variant are in linkage disequilibrium remains unknown. Therefore, further study in the same sample is required to determine the association among these variants in the NR2B gene.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, Ohtsuki et al reported eight variants encoding exons in the 3′-untranslated region of the hNR2B gene, some of which were significantly associated with schizophrenia. 18 In the present study, we sequenced 5′-upstream nucleotides of the hNR2B gene and identified a novel T-200G variant that was significantly associated with schizophrenia. We suggest that this variant is involved in glutamate dysfunction leading to the development of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%